Reliability-Based Optimum Design of Dome Truss Structures through Enhanced Vibration Particle System - Pedram Hosseini; Nasibeh Hatami; Seyed Rohollah Hoseini Vaez (Journal of Rehabilitation in Civil Engineering)
Recent years have seen a significant increase in structural engineers' interest in the assessment of reliability and structural safety. The Reliability-Based Design Optimization (RBDO) method has been utilized to create the most efficient and safe design of structures. Although there have been several theoretical advances in reliability analysis, computational barriers still occur in realistic problems. The purpose of this paper is to provide a process for the optimization of dome truss structures based on reliability. For this purpose, a flowchart including the process of Deterministic Design Optimization (DDO) and RBDO was presented. An evaluation of the reliability of the structure is made by using random variables to represent uncertain parameters. Throughout this study, random variables such as the module of elasticity, material density, and the cross-sectional area of the elements are considered. The deterministic constraints for DDO are the vertical displacement of free nodes and the demand-capacity ratio of all members. Also, reliability index 3 is set as the minimum target reliability index. Meta-heuristic algorithms can be used to achieve optimal design and appropriate safety since mathematical calculations are time-consuming. As part of this study, the Enhanced Vibration Particle System (EVPS) and Vibration Particle System (VPS) have been applied to DDO (incorporating reliability assessment) and RBDO of three dome trusses. The results were obtained using the processes of RBDO and DDO without any deviation in the acceptable space. The solution of RBDO will increase the weight and safety of structures.